2022
DOI: 10.3389/fimmu.2022.908558
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Complete Remission of a Patient With Metastatic Gastric Cancer Treated With Nivolumab Combined With Chemotherapy After Palliative Surgery

Abstract: Metastatic advanced gastric cancer, for which treatment strategies are extremely limited, has a poor prognosis. Complete remission is rare. Patients usually lose the opportunity of therapeutic surgery because the lesions cannot be completely removed, although it can greatly prolong their survival time. Palliative surgery usually suggests bad outcomes. In recent years, the immune checkpoint inhibitor (ICI) nivolumab has shown significant efficacy in the treatment of advanced gastric cancer. However, its applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 62 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…With the new clinical development of immune checkpoint inhibitors, there have been some reports of nivolumab being used successfully in the perioperative period. We used PubMed to search for case reports in English with the key terms “Gastric Cancer”, “Stage IV”, “Nivolumab”, and “CR”, and summarized them in Table 1 [ 9 , 13 24 ]. The definition of CR in this search also included clinical and pathological CR.…”
Section: Discussionmentioning
confidence: 99%
“…With the new clinical development of immune checkpoint inhibitors, there have been some reports of nivolumab being used successfully in the perioperative period. We used PubMed to search for case reports in English with the key terms “Gastric Cancer”, “Stage IV”, “Nivolumab”, and “CR”, and summarized them in Table 1 [ 9 , 13 24 ]. The definition of CR in this search also included clinical and pathological CR.…”
Section: Discussionmentioning
confidence: 99%
“…13 However, with the progression of anticancer drug therapy, some case reports state that curative surgery for stage IV gastric cancer becomes possible after pre-operative treatment. [7][8][9][14][15][16] An international multicenter retrospective study verified the significance of conversion surgery and found that the median survival time of all resected patients who received pre-operative treatment for stage IV gastric cancer was 36.7 months. Those of R0, R1, and R2 resection were 56.6, 25.8, and 21.7 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…31 Some case reports of conversion surgery use these agents. [7][8][9] However, the prognostic effect of pre-operative treatment using chemotherapy plus ICI for stage IV gastric cancer is still unclear, as with chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations